Correlação entre a resistência nasal e diferentes parâmetros da rinometria acústica em crianças e adolescentes com e sem rinite alérgica - Wandalsen, Gustavo Falbo [UNIFESP] (2012)
Acoustic rhinometry and rhinomanometry are important tests used to assess nasal function. The degree to which the parameters of these tests are correlated is yet to be established. OBJECTIVE: This paper aimed to study the correlations between nasal resistance (NR) and acoustic rhinometry parameters in children and adolescents with allergic rhinitis and controls. METHOD: Twenty patients with allergic rhinitis and 20 controls were enrolled. NR, volumes (V4, V5, V2-5), and minimal cross-sectional areas (MC1, MC2) were measured in three moments: baseline, after induction of nasal obstruction and after topical decongestant administration. RESULTS: Patients with allergic rhinitis had significant correlation between NR and all volumes (V5: r = -0.60) and with MC2. Among controls, MC1 was the parameter with the strongest correlation with NR at baseline (r = -0.53) and after decongestant administration. In the combined analysis, V5 had the highest correlation coefficients at baseline (r = -0.53), after obstruction (r = -0.58) and after decongestant (r = -0.46). CONCLUSIONS: Our data showed that NR and acoustic rhinometry parameters have negative and significant correlations. Nasal volumes are, in general, better correlated than minimal cross-sectional areas. V5 was the parameter with the highest correlation in the rhinitis group and in the combined analysis.